Nonlinear Mixed‐Effects Model Development and Simulation Using nlmixr and Related R Open‐Source Packages. (16th July 2019) - Fidler, Matthew; Wilkins, Justin J.; Hooijmaijers, Richard; Post, Teun M.; Schoemaker, Rik; Trame, Mirjam N.; Xiong, Yuan; Wang, Wenping
Abstract : nlmixr is a free and open‐source R package for fitting nonlinear pharmacokinetic (PK), pharmacodynamic (PD), joint PK‐PD, and quantitative systems pharmacology mixed‐effects models. Currently, nlmixr is capable of fitting both traditional compartmental PK models as well as more complex models implemented using ordinary differential equations. We believe that, over time, it will become a capable, credible alternative to commercial software tools, such as NONMEM, Monolix, and Phoenix NLME.